Analisis Kinerja Simpang Tak Bersinyal Dengan Metode PKJI 2014 - Abdu Rizal Zhafiri (Jurnal Mahasiswa Kreatif, 2023)
The city of Surabaya is one of the cities in Indonesia, the second largest in Indonesia after the city of Jakarta. The city of Surabaya is said to be a metropolitan city that has experienced quite serious problems in traffic, namely congestion. As happened at the Simpang Jl. Raya Mastrip and Jl. Jemb. Along Baru, which is an intersection with type 322, has 3 arms. Geometric Intersection Jl. Raya Mastrip and Jl. Jemb. Along Baru it can be seen that the road width is 7 meters with 2 lanes with a lane width of 3.5 meters each without a road median. The method used in this study is to use the Indonesian Road Capacity Guidelines (PKJI). The results of calculating the volume of traffic flow at the Intersection of Jalan Raya Mastrip and Jalan Jemb. Throughout New. Obtained on Friday 9 April 2021 with peak conditions at 08.00 - 09.00 obtained qTOT = 14128 kend/hour and 4883 cur/hour. The value of Intersection Capacity (C) obtained a value of = 2593 cur/hour. Obtained delay of = 21 sec/cur value Dj = 1.9. From the results of the calculation of the degree of saturation (Dj), the results of the calculation of the lower limit and upper limit of the Queue Opportunity are obtained by PA = 33% - 77%. Based on the characteristics of the Level Of Services (LOS) or commonly called the service level, the value obtained is Dj = 1.9, the service level is D.